Characterization of Skin Microbiome in Tinea Pedis - Liu, Xiaoping (Indian J Microbiol, 2019)
Tinea pedis has been associated with Trichophyton rubrum infection. However, it’s not clear whether other microbes were implicated in disease pathogenesis. The composition of microbial communities of patients with tinea pedis and healthy controls were analyzed to identify the characteristics of tinea pedis and differences associated with clinical patterns. We found that microbial community structures were different in patients with tinea pedis compared with healthy controls. Moreover, skin microbiome varied in different forms of tinea pedis. Healthy controls exhibited greater fungal diversity than patients with tinea pedis. In patients with tinea pedis, the dominant bacterial and fungal genera were Staphylococcus and Trichophyton. Compared with healthy controls, Corynebacterium tuberculostearicum was decreased and T. rubrum was increased. C. tuberculostearicum was more abundant in vesicular tinea pedis than in hyperkeratotic and interdigital tinea pedis. Interdigital tinea pedis had a higher detection rate of Corynebacterium minutissimum and T. rubrum than the other forms. These results indicated that bacterial microbes may take part in the development of tinea pedis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12088-019-00816-y) contains supplementary material, which is available to authorized users.